Draft Third Five-Year Plan Large Scale and Medium industries - Planning Commission (Planning Commission, 1960)
In G.O. Mb. No. 1494, Public (Planning and Development), dated 14th May 1959, the Madras Government constituted a number of Working Groups for preparing a draft outline of the Third Five- Year Plan for the State in the various sectors. the Working Group on Industries including Industrial Co-operatives was set up with the Secretary to Government, Industries, Labour and Co-operation Department, as Chairman and Secretary to Government, Finance Department, Director of Industries and Commerce and Additional Secretary to Government (ex-Officio), Industries, Labour and Co-operation (Special) Department, Joint Development Commissioner, Director of Khadi, Registrar of Co-operative Societies and the Director of Handlooms as Members.
Industries, Labour and Co-Operation Department